Answer:
7s
Step-by-step explanation:
We can combine this because they are like terms.
Answer:
Angle 1,4 and 7
Step-by-step explanation:
I know I know
18÷(5-2)
18÷3
6 is the answer
Answer:
![(B)r=\dfrac{85}{12}](https://tex.z-dn.net/?f=%28B%29r%3D%5Cdfrac%7B85%7D%7B12%7D)
Step-by-step explanation:
Given a circle centre J
Let the radius of the circle =r
LK is tangent to circle J at point K
From the diagram attached
Theorem: The angle between a tangent and a radius is 90 degrees.
By the theorem above, Triangle JLK forms a right triangle with LJ as the hypotenuse.
Using Pythagoras Theorem:
![(6+r)^2=r^2+11^2\\(6+r)(6+r)=r^2+121\\36+6r+6r+r^2=r^2+121\\12r=121-36\\12r=85\\r=\dfrac{85}{12}](https://tex.z-dn.net/?f=%286%2Br%29%5E2%3Dr%5E2%2B11%5E2%5C%5C%286%2Br%29%286%2Br%29%3Dr%5E2%2B121%5C%5C36%2B6r%2B6r%2Br%5E2%3Dr%5E2%2B121%5C%5C12r%3D121-36%5C%5C12r%3D85%5C%5Cr%3D%5Cdfrac%7B85%7D%7B12%7D)
The length of the radius, ![r=\dfrac{85}{12}](https://tex.z-dn.net/?f=r%3D%5Cdfrac%7B85%7D%7B12%7D)